2015
DOI: 10.1016/j.juro.2014.12.095
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Which Patients will Experience Resolution of Detrusor Overactivity after Transurethral Resection of the Prostate?

Abstract: Advanced patient age together with low maximum cystometric capacity, and early and high detrusor overactivity amplitude are the most important predictors of persistent detrusor overactivity after relief of bladder outlet obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 18 publications
2
42
3
Order By: Relevance
“…also showed that advanced patient age together with low MCC and early and high amplitude uninhibited contractions are the most important clinical predictors of persistent DO after BOO is relieved. 17 The results were similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…also showed that advanced patient age together with low MCC and early and high amplitude uninhibited contractions are the most important clinical predictors of persistent DO after BOO is relieved. 17 The results were similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Classification of DO may be according to its onset, amplitude, and recurrence during filling cystometry. Urodynamic risk factors for persistent DOA include Kageyama type I or II DO (early onset or phasic), amplitude >40 cmH 2 O, and maximum cystometric capacity <250 mL) . Clinical factors have also been related to persistent DO/OAB postoperatively (eg advanced age) …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Antunes et al studied 46 patients with BPO who underwent TURP from 2011 to 2012. Urodynamics were carried out preoperatively and 12 months postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…This de novo urge incontinence causes significant stress and anxiety not only for the patients but also for the surgeons. In a recent prospective study of persistent storage symptoms after successful relief of BOO, urodynamic DO was persistent in approximately 40% of the patients [6].…”
Section: Introductionmentioning
confidence: 98%